2019
DOI: 10.3892/br.2019.1186
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Toxoplasma gondii antibodies attach to mouse cancer cell lines but not normal mouse lymphocytes

Abstract: Toxoplasma gondii (T. gondii) is prevalent intracellular parasite and a cause of worldwide infection in the human population. An inhibitory effect of this parasite on cancer growth has been demonstrated in cell culture and animal models. To determine whether the anticancer activities of T. gondii are associated with host immune response, in the current study the reactivity of anti-T. gondii antiserum with the surface of cancer cell lines was investigated. Anti-T. gondii antibodies were raised in rabbit and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This study showed that treatment of Tumor bearing mice with Toxoplasma gondii lysate or irradiated tachyzoite resulted in decreasing tumor volume. In agreement with results of this investigation, there are scientific evidences demonstrating that T.gondii have desired effect on tumor suppression [5][6][7][8][9]. In experiments with Toxoplasma gondii it has been shown that injection of live tachyzoites of this parasite resulted in decreasing growth of lung [15] and melanoma [16] cancers in mice.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study showed that treatment of Tumor bearing mice with Toxoplasma gondii lysate or irradiated tachyzoite resulted in decreasing tumor volume. In agreement with results of this investigation, there are scientific evidences demonstrating that T.gondii have desired effect on tumor suppression [5][6][7][8][9]. In experiments with Toxoplasma gondii it has been shown that injection of live tachyzoites of this parasite resulted in decreasing growth of lung [15] and melanoma [16] cancers in mice.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, there are a lot of evidences about anti-cancer effects of parasites in human population, in animal model and in laboratory experiments [3,8,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies involving parasites demonstrate that bioactive molecules and parasites promote antitumor effects, such as Strongyloides stercoralis, Toxoplasma gondii, Plasmodium, and Trypanosoma cruzi (Plumelle et al, 1997;Kim et al, 2007;Chen et al, 2011;Lukasiewicz and Fol, 2018). It has been demonstrated that parasite anticancer activity is mediated by antitumor immunity induction and immunomodulation (Ubillos et al, 2016;Mohamadi et al, 2019;Riaz, 2019), gene regulation (Lu et al, 2019), and anticancer effects by parasite molecule production (Atayde et al, 2008;Valck et al, 2010;Darani and Yousefi, 2012;Ramírez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%